2015
DOI: 10.1210/jc.2014-2190
|View full text |Cite
|
Sign up to set email alerts
|

Smoking as an Effect Modifier of the Association of Calcium Intake With Bone Mineral Density

Abstract: Even though the present results cannot rule out that smoking-associated differences in calcium absorption exist, they do suggest that smoking behavior does not have any relevant impact on the beneficial effects of calcium intake on bone mineral density at the population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…This is similar to the Ca intake reported in the general population [37]. Adequate Ca intake from the diet is associated with decreased risks for fracture, non-fatal CVD, stroke, and all-cause mortality [38] however, no evidence suggests that smoking is detrimental to Ca nutrition [39]. …”
Section: Discussionsupporting
confidence: 69%
“…This is similar to the Ca intake reported in the general population [37]. Adequate Ca intake from the diet is associated with decreased risks for fracture, non-fatal CVD, stroke, and all-cause mortality [38] however, no evidence suggests that smoking is detrimental to Ca nutrition [39]. …”
Section: Discussionsupporting
confidence: 69%
“…The correlational analysis did not find a significant effect for serum osteocalcin (OC) or tartrate resistant acid phosphatase isoenzyme 5b (TRACP 5b) [ 55 ]. The interaction between smoking and other compounds found smoking with calcium intake did not reach statistical significance for BMD [ 19 ]; however, elderly women with the lowest tertile of choline who were exposed to nicotine had the highest risk for low BMD (OR=4.56, 95%CI: 1.87-11.11) [ 49 ]. One prospective study found growth hormone (GH) therapy after 3-5 years did not significantly improve total BMC of smokers (P = 0.09) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Además, el hábito tabáquico también se ha relacionado con el fenómeno de osteoporosis. Algunos autores defienden que el consumo de tabaco tiene una correlación negativa con la ingesta de calcio, haciendo referencia directamente al estilo de vida de los individuos 21 . En nuestro estudio observamos como los fumadores muestran niveles de calcio en sangre más altos, en consonancia con otros autores que muestran como el tabaco produce un aumento de la reabsorción ósea, lo cual justificaría niveles más elevados de calcio 22 .…”
Section: Discussionunclassified